The student's companion to sociology (Malden, MA : Blackwell, 1997)
This book is about: Sociology: Engaging with the social world; Sociology and its traditions; Contemporary sociological engagement; Doing sociology: Study and research; Directory and resources; ...
Keywords: Sociology; Sociology; Sociologists -- Vocational guidance